1997
DOI: 10.1073/pnas.94.4.1298
|View full text |Cite
|
Sign up to set email alerts
|

Triplet repeat polymorphism in the transmembrane region of the MICA gene: A strong association of six GCT repetitions with Behçet disease

Abstract: A member of a novel family of the human major histocompatibility complex (MHC) class I genes termed MIC (MHC class I chain-related genes), MICA, has been recently identified near the HLA-B gene on the short arm of human chromosome 6. The predicted amino acid sequence of the MICA chain suggests that it folds similarly to typical class I chains and may have the capacity to bind peptides or other short ligands. Therefore, MICA is predicted to have a specialized function in antigen presentation or T cell recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
307
0
5

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 353 publications
(326 citation statements)
references
References 29 publications
14
307
0
5
Order By: Relevance
“…13 The STR consists of (GCT)n repeats, corresponding to alanines in the protein. 14 Eight alleles have been described, A4, A5, A6, A7, A8, A9 and A10, with 4-10 GCT repetitions, and A5.1, which has a G insertion, causing a frame shift mutation that creates a premature In the populations from this study it could also be *00804. In the populations from this study it is MICA*01801.…”
Section: Introductionmentioning
confidence: 79%
“…13 The STR consists of (GCT)n repeats, corresponding to alanines in the protein. 14 Eight alleles have been described, A4, A5, A6, A7, A8, A9 and A10, with 4-10 GCT repetitions, and A5.1, which has a G insertion, causing a frame shift mutation that creates a premature In the populations from this study it could also be *00804. In the populations from this study it is MICA*01801.…”
Section: Introductionmentioning
confidence: 79%
“…This evidence begins in the HLA-B locus, where associations between BD and several alleles in addition to HLA-B*51 have been reported (8)(9)(10). It also has been argued that variants in or around MHC class I polypeptide-related sequence A (MICA), the centromeric neighbor of HLA-B that encodes the MHC-I chain-related sequence A, contribute to BD susceptibility (11). However, efforts to parse the effects of MICA and HLA-B alleles definitively have been confounded by their particularly strong LD (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…It also has been argued that variants in or around MHC class I polypeptide-related sequence A (MICA), the centromeric neighbor of HLA-B that encodes the MHC-I chain-related sequence A, contribute to BD susceptibility (11). However, efforts to parse the effects of MICA and HLA-B alleles definitively have been confounded by their particularly strong LD (11)(12)(13)(14). Additionally, HLA-A has been identified as a BD susceptibility locus in numerous studies (2,3,(14)(15)(16)(17), and it has been suggested that HLA-C contributes to BD risk, as well (14).…”
mentioning
confidence: 99%
“…1). Genes within this region have been implicated in the susceptibility to several autoimmune diseases including Behçet's disease, 14,15 Addison's disease, 16 and insulin-dependent diabetes mellitus. 17 MICA and MICB genes encode major histocompatibility complex (MHC)-like molecules with 3 extracellular domains, a transmembrane segment, and a cytoplasmatic tail.…”
mentioning
confidence: 99%